Carbon nanotube-based van der Waals heterojunction electrodes for high-performance intrinsically stretchable organic photoelectric transistors. (August 2021) - Liu, Kai; Bian, Yangshuang; Kuang, Junhua; Li, Qingyuan; Liu, Yanwei; Shi, Wei; Zhao, Zhiyuan; Huang, Xin; Zhu, Zhiheng; Guo, Yunlong; Liu, Yunqi
Highlights: A novel and general strategy on CNT-based heterojunction electrodes by pentacene modification layer to enable high-performance intrinsically stretchable organic photoelectric transistors is proposed. The resulting stretchable organic transistors exhibit simultaneously improved electrical characteristics, strain-tolerance capabilities and performance stability. The Ion /Ioff ratio is up to 10 7, which is the highest value for the stretchable transistors reported currently. These are the first intrinsically stretchable organic phototransistors with desirable photoswitching performances and high strain tolerance developed. Abstract: Intrinsically stretchable organic field-effect transistors (STOFETs) that behave much like skin, have garnered widespread attention and demonstrated potential to more comfortable wearing electronics. Despite considerable efforts being exerted in stretchable hybrid polymeric semiconductors to achieve high-mobility and high-stretchability STOFETs, carbon nanotubes (CNTs) as ideal electrode materials, its interfacial quality seldom attracts research interests. Herein, we demonstrate a novel and general strategy on flexible CNT-based heterojunction electrodes by pentacene modification layer to enable high-performance and functional STOFETs. Pentacene transition layer can reduce the surface roughness and tune the heterogeneity of functional groups on the CNT thin film, as well as enhance the compatibility and van der Waals contact between CNT electrodes and organic semiconductors. The experimental results reveal that the carrier mobility of the resulting STOFETs increases by 2-3 times and the subthreshold slope decreases by 5 times compared with unmodified devices. The on-current/off-current ratio reaches nearly 10 7, which is approximately 1000 times as high as unmodified devices, and the highest value for stretchable organic transistors reported so far. Furthermore, STOFETs with heterojunction electrodes demonstrate better performance homogeneity and higher strain-independent capability. Noteworthy, these are the first intrinsically stretchable organic phototransistors (STOPTs) with superior photoswitching performances and high strain tolerance developed. Graphical Abstract: Image, graphical abstract